The Impact of Grants and Scholarships on Students’ Academic Achievement and Educational Equity: A Comparative and Analytical Study - Ochilova Maftuna (Zien Journals, 2025)
During the last few years, university scholarship programs have emerged as an important and fundamental tool guaranteeing inclusion among students in higher education. These initiatives are in need of keeping and promoting decrease of socioeconomic obstacles that limit students’ opportunities and improve activeness, study enthusiastic and academic success among them. This research aims to analyze the impacts of scholarships on academic journey, continuity of university students. The analyzed variables encompass demographic characteristics, academic progress, and performance indicators such as cumulative GPA, credits enrolled, completed, and passed, as well as success and achievement rates. Different approaches and many experiments are conducted to differentiate student performance and roles of scholarships to show how free education can improve success. Advanced statistical methods were applied to detect meaningful patterns and trends. Moreover, this study contributes empirical evidence relevant to the formulation and evaluation of inclusive educational policies that advance equity in higher education.
Keywords: University scholarships; tuition; free education.